Science education in early childhood education mediated by technologies: a systematic review - Pino-Perdomo, Felipe (2023)
ABSTRACT: Introduction: The development of scientific competencies in early childhood education allows the understanding of the world that surrounds the infant, historically it has been done from the exploration of the environment, however, the use of technologies is a current need in the learning processes, continuous improvement and contextualization of pedagogical practice in early childhood education. Objective: to identify training trends in scientific competencies in early childhood education focusing on teaching strategies and didactic resources mediated by educational technology. Methodology: the review was based on a qualitative approach, a search was carried out in the SCOPUS database characterizing the title of the article, abstract and keywords with the following search criteria: early AND childhood AND science AND education AND educational AND technology, applying the filter Source type: Journal in the period between 2007 and 2022 for a subsequent hermeneutic analysis taking into account the categories of teaching strategies and didactic resources. Results: it was found that there is a strong tendency to use the Science, Technology, Engineering and Mathematics -STEM- models; in the case of didactic resources, the use of robots, online and interactive educational applications, websites, use of mobile devices and software for tactile use and computer equipment stand out in the literature reviewed. Conclusions: the present study allows highlighting that it is important to take into account technological, pedagogical and content limitations when implementing teaching strategies in early childhood education, since these limitations can affect the success of educational practices and the ability of teachers to teach scientific competencies effectively.